Validity test of digital learning content in social science education for junior high schools in Singaraja city - Utami, Anak Agung Istri Dewi Adhi; Suastika, I Nengah; Mudana, I Wayan; Sriartha, I Putu; Sujana, I Putu Windu Mertha; Budiarta, I Wayan; Sidaryanti, Ni Nyoman Asri; G. Vann, Michael (Universitas Negeri Yogyakarta, 2025)
This research aims to analyse the needs for developing digital learning media in Social Sciences learning in junior high schools in Singaraja City. This study used qualitative research methods. The process of developing learning media must be carried out by testing construct validity and empirical validity. Material experts, media experts and language experts will carry out validity testing. The results of the analysis of social science education material experts assessed the validity score of the material to be 93, or the criteria